Scroll, Stress, Repeat: Online FOMO (Fear of Missing Out) dan Kondisi Kesehatan Mental Gen-Z - Jasmine Mashita Johandi; Novita Fitri Apriliana; Dinar Saputra (Inquiry: Jurnal Ilmiah Psikologi, 2026)
In the digital era, Online Fear of Missing Out (ON-FoMO) has become increasingly common, especially among Generation Z. ON-FoMO refers to anxiety arising from the fear of missing trends, information, or online social activities, which can reduce productivity and trigger negative emotions such as inferiority and life dissatisfaction. This study aims to describe ON-FoMO levels and psychological well-being among university students. Using a descriptive quantitative method with a cross-sectional design, data were collected through snowball sampling from 305 students. The measurement tools used in this study were the ON-FoMO Scale and the SRQ-20 Scale The ON-FoMO Scale assessed four dimensions—anxiety, need to belong, addiction, and need for popularity—while the Self-Reporting Questionnaire (SRQ-20) measured psychological symptoms across energy, cognition, physiology, and anxiety dimensions. Descriptive statistical analysis revealed that most respondents had moderate to high ON-FoMO, particularly those aged 20–23, with females making up 74.43% of participants. Mental health conditions were generally mild to moderate, also dominated by the 20–23 age group (47.9%). These findings highlight the need for strategies to strengthen Generation Z’s mental resilience against digital social pressures, emphasizing early interventions, psychoeducation, and healthy online engagement to mitigate ON-FoMO’s psychological impact.